Smoking cessation knowledge and perceptions of cancer care providers at six Latin American cancer institutions - Irene Tamí-Maury; Hector Garcia; Modupe Onigbogi; Julia Ismael; Javier Manrique; Vinicius Vazquez; Carlos Rojas; Laura Suchil (Revista Panamericana de Salud Pública, 2022)
Objective. To assess the characteristics, self-reported tobacco use, knowledge, and perceptions about smoking cessation among cancer care providers (CCPs), as well as perceived barriers to inform interventions that can potentially improve quitting rates and the prognosis of cancer patients in Latin America. Methods. A cross-sectional study was conducted among 996 CCPs in six cancer institutions located in Argentina, Brazil, Colombia, Mexico, and Peru. An online survey consisting of 28 close-ended questions adapted from the 2012 International Association for the Study of Lung Cancer survey and the Global Adult Tobacco Survey was administered. Results. The majority of CCPs, ranging from 86.1% in Mexico to 95.9% in Brazil, agreed or strongly agreed that smoking cessation should be integrated into cancer treatment. However, inadequate training on smoking cessation was reported by 66.9%, 69.4%, 70.4%, 72.9%, 85.8%, and 86.4% in Mexico, Colombia (Floridablanca), Argentina, Peru, Brazil, and Colombia (Medellín), respectively, and this difference was statistically significant (p < 0.001). Moreover, current cigarette smoking prevalence among CCPs was 2.5% in Brazil, 4.6% in Peru, 6.3% in Colombia (Floridablanca), 10.4% in Colombia (Medellín), 11.5% in Mexico, and 15.1% in Argentina, showing a statistically significant difference (p < 0.001). Conclusions. Efforts in Latin America should be geared toward assisting CCPs with their quitting efforts and training in smoking cessation practices aimed at achieving a better prognosis and improving cancer patients’ quality of life.